Optimal Taxation Policies in the EMS : A Two-Country Model of Public Finance. (IMF Working Papers; Working Paper ;, 1989)
This paper analyzes, in a public finance context, how the optimal use of the inflation and the consumption tax is affected by incorporating into the model constraints on policy decisions that are likely to develop in the context of the EMS by 1992. Two main questions are addressed: first, how the constraint of having to share a common inflation tax, in order to preserve fixed-exchange rates, influences the optimal policy decisions concerning the inflation tax; secondly, how the harmonization of consumption taxes affects the spread between national inflation rates, and hence the probability of having to resort to realignments.